Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Nasabah: (Survey Pada Nasabah PT. Bank Rakyat Indonesia, Tbk Cabang Majalengka - Barin Barlian (JURNAL BUANA INFORMATIKA CBI, 2018)
The purpose of this study is to know and analyze Product Quality and Service Quality to Customer Satisfaction. The object to be studied is PT. Bank Rakyat Indonesia, Tbk Cabang Majalengka. The research method used is survey method. The collection of data obtained through interviews, questionnaires and literature. Population in this research is Customer at PT. Bank Rakyat Indonesia, Tbk Cabang Majalengka. By using path analysis, the study found that partially, Product Quality and Service Quality have significant influence on Customer Satisfaction. Simultaneously, Product Quality and Service Quality has a significant influence on Customer Satisfaction, So the hypothesis was verified.